Multiparasitism in Spain in a Korean Visiting Friends and Relatives: Case Report and Review of Imported Cases of Clonorchis sinensis in Europe - Paola Cociancic; Jacklyn Comas; J. Guillermo Esteban (Clinical Case Reports)
ABSTRACT We report a case of imported Clonorchis sinensis infection under the modality of “visiting friends and relatives.” Clonorchis was not diagnosed initially, and a second stool sample was necessary. It is important that health personnel collect detailed information from the patient and be trained in parasitological diagnosis of imported infections.